Description of three new cicada species in the genus Yoyetta Moulds (Hemiptera: Cicadidae: Cicadettinae), from eastern Australia - Emery, David L.; Emery, Nathan J.; Popple, Lindsay W. (Zootaxa, 2025)
Three new cicada species from eastern New South Wales and Queensland, Australia, are described in the genus Yoyetta Moulds, 2012. Yoyetta darug sp. nov. is most common in the western Sydney area in New South Wales (NSW); Y. psammitica sp. nov. has been found in the Bylong Valley and Warrumbungle National Park in NSW and Carnarvon Station in central Queensland; Y. fumea sp. nov. has been found principally in the Southern Highlands of NSW. The new species are closely related to Y. humphreyae Moulds & Popple and Y. corindi Popple & Emery in their morphology and song, and are broadly allied to Y. tristrigata (Goding & Froggatt). Within each species a description, as well as a section on distinguishing features, distribution, habitat and behaviour, and calling song structures are provided and illustrated where appropriate. Additional location records for Y. humphreyae are included. A revised key to species for the genus Yoyetta Moulds is also provided.